ANALYSIS OF HANDLING REVERSE LOGISTICS (CASE STUDY OF WASHING MACHINE MEGAMOUTH SERIES AT PT. SHARP ELECTRONIC INDONESIA) - Muhammad Basyar Azzuhri (Journal of Social and Economics Research, 2024)
This journal is about reverse logistics at PT. Sharp Electronics Indonesia . Even it is not popular when compared to forward logistics. Reverse Logistics aims to save the value of the product so that it can be reused so that the goods should be discarded and do not have value to have a return value and can be resold so as to increase profits for the company. PT. Sharp Elektronics Indonesia is a company engaged in electronics, which is produced Refrigerator, washing machine, TV, etc. The main problem faced by PT. Sharp Electronics Indonesia is a Reverse Process Handling on washing machine products. Reverse logistics activities conducted at PT. Sharp Electronic Indonesia is Gatekeeping, Refurbish and Remanufacturing, Negotiation and Financial Management. To make the reverse activity more optimal, the researcher suggests the company to apply other policies besides those that have been applied, namely Compacting Disposition Cycle Time (CDCT) policy that is related to how to reduce the disposition process cycle and Asset Recovery policy in which the company resells goods suffered damage without any renewal process.